Early weight trends in preterm babies post discharge - Fadnis, Madhura P.; Prabhu, Sanjay; Prabhu, Shakuntala S. (International Journal of Contemporary Pediatrics, 2020)
Background: Prematurity is the major determinant of morbidity and mortality in newborns. Infants born preterm are at increased risk for impaired growth. The postnatal growth pattern is dependent on biological factors like birth weight, gestational age, sex and intrauterine growth. The present study was undertaken to study the risk factors associated with the preterm delivery and to study the weight gain pattern among the preterm neonates after NICU discharge for a period of one month. Aims and objectives to study the risk factors associated with preterm and to analyze the weight gain pattern of the preterm till one-month post NICU discharge. Methods: A total of 40 preterm were included during the study period of 2 months, the various maternal risk factors were studied and correlated with preterm delivery. The neonatal complications were studied. The neonates were divided on the basis of their gestational age and birth weight. They were then followed for a period of 1-month post NICU discharge. Results: There was significant correlation of lower gestational age with neonatal complications and prolonged duration of hospitalization. The weight gain pattern was highly variable with a maximum gain of 188 gm after first week of NICU discharge. Weight gain was significantly more in first week after discharge amongst neonates who had birth weight less than 1.5 kg and also the total weight gain was significantly more in neonates who weighed less than 1.5 kg at birth. Conclusions: Lower gestational age group 28-32 weeks was significantly associated with neonatal complications and prolonged duration of hospitalization. Immediate follow up of the preterm is necessary as there is wide variability in the weight gain pattern in various gestational age groups.